Fluid-structure interaction for large scale complex geometry and non-linear properties of structure - Roszak, R.; Posadzy, P.; Stankiewicz, W.; Morzyński, M. (Archives of Mechanics, 2009)
In this paper fluid-structure interaction, taking into account the nonlinearity of structural models, is concerned. This phenomenon has important influence in many aeronautical applications. The method and developed system is demonstrated on NACA-0012 wing mounting, made of non-linear springs and include structures with non-linear materials, modelled by Neo–Hooke and Mooney–Rivlin models, like flexible delta wing. For the first flow the comparison with experiment made in Institute of Aviation Warsaw is presented. For both mentioned above models, the linear and non-linear analysis are presented and the critical flutter speeds are determined. Finally, aeroelastic simulation of full I23 aircraft configuration presents the capability of used numerical codes to analyze large-scale complex geometries. All computations were carried out in parallel environment for CFD mesh of order of millions tetrahedral elements.